Health exposure of users of indoor sports centers related to the physico-chemical properties of particulate matter - Bralewska, K.; Rogula-Kozlowska, W. (Building and Environment, 2020)
The aim of this study was the identification of the factors that determine the concentrations of particulate matter (PM) in the indoor air of a selected sports facility, as well as the assessment of the health exposure of the sports facility users (pupils aged 8-18 years, trainers and athletes aged 21-40 years) to PM and its components. The mass concentration of size-resolved (PM1, PM1-2.5, PM2.5-4, PM4-10, PM10-100) total suspended particles (TSP) was measured using DustTrak DRX devices. Measurements were conducted for 8?h a day, simultaneously inside and outside a typical sports hall in Warsaw, for 20 days each in the heating (16/10/-20/11/2017) and non-heating (18/05/-21/06/2017) seasons. At the same time, samples of PM4 and TSP were taken (GilAir 3 aspirators) to determine ambient concentrations of PM-bound metals and polycyclic aromatic hydrocarbons (PAH). The main factor affecting TSP concentration in the sports facility was dust resuspension; it was especially visible in variations of coarse PM concentrations. The concentrations of fine PM as well as PM-bound metals and PAHs inside the hall were determined mainly by outdoor sources - combustion of fossil fuels and non-traffic emissions. The incremental lifetime cancer risk (ILCR) related to the exposure of the sports hall users to PM-bound metals and PAHs was in the range of 6.9E-05-1.1E-04; it was higher than that calculated for PM-bound metals and PAHs in atmospheric air (5.4E-05-9.8E-05). The highest ILCR concerns pupils, which inside the sports facility is above the acceptable risk level value of 1E-04.